2000
DOI: 10.1016/s1074-7613(00)80220-4
|View full text |Cite
|
Sign up to set email alerts
|

Structural Basis of Peptide Binding and Presentation by the Type I Diabetes-Associated MHC Class II Molecule of NOD Mice

Abstract: al., 1999). Nevertheless, a consensus I-A g7 binding motif has been difficult to establish from the sequence analysis and binding studies of naturally processed and synthetic peptides. One complication arises from the proposed weak interaction of I-A g7 with peptides (Reich et

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
181
2

Year Published

2002
2002
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 177 publications
(191 citation statements)
references
References 46 publications
8
181
2
Order By: Relevance
“…The absence of this salt bridge in the case of diabetogenic class II MHC molecules generated a P9 pocket that was wider, shallower and open towards the Cterminus [9][10][11]. However, the effect of these unique structural features on peptide selection remained unclear: earlier reports that analyzed binding interactions with synthetic peptides or peptide libraries suggested that diabetogenic MHC molecules bound peptides promiscuously with little or no specificity [12][13][14][15].…”
Section: Biochemical Structural and Functional Properties Of Diabetementioning
confidence: 99%
See 1 more Smart Citation
“…The absence of this salt bridge in the case of diabetogenic class II MHC molecules generated a P9 pocket that was wider, shallower and open towards the Cterminus [9][10][11]. However, the effect of these unique structural features on peptide selection remained unclear: earlier reports that analyzed binding interactions with synthetic peptides or peptide libraries suggested that diabetogenic MHC molecules bound peptides promiscuously with little or no specificity [12][13][14][15].…”
Section: Biochemical Structural and Functional Properties Of Diabetementioning
confidence: 99%
“…Initial binding studies of the B:(9-23) peptide to soluble I-A g7 in detergent free conditions revealed poor binding and fast dissociation rates [10,13,14,40]. The IC 50 values for the B:(9-23) peptide were measured in the 5-10 μM range at endosomal pH and the half-life of the complexes was less than two hours.…”
Section: Weak Mhc Binding Peptides and Autoreactivity: The Case Of Thmentioning
confidence: 99%
“…These residues are known to be critical for the peptide-binding function of the class II molecule. [59][60][61][62][63] In particular, aspartic acid (Asp) at residue 57, which is in pocket 9 of the HLA-DQB1 molecule, is encoded by a HLA-DQB protective allele, whilst an alanine, valine or serine residue at the same position characterises predisposing alleles. In the absence of aspartic acid the charge at the 'right hand' end of the peptide-binding pocket becomes more positive.…”
Section: Hla-encoded Susceptibility To T1dmentioning
confidence: 99%
“…Alternatively, or in addition to the loss of central tolerance, abnormalities of peripheral tolerance can be present, with some HLA alleles presenting specific peptides (such as islet cell peptides) to mature T lymphocytes that did not undergo negative selection. A number of investigators have advanced the hypothesis that HLA alleles associated with susceptibility to autoimmunity could be ªunstableº [54,55,56]. Though this hypothesis is feasible it is difficult to reconcile with the same HLA haplotypes associated with protection from diabetes and susceptibility for multiple sclerosis (e. g. DR2, DQB1*0602) or with the strong binding of insulin peptide B:9±23 to DQ8 whose crystal structure has recently been solved [57].…”
Section: Mechanisms Of Diabetogenicity Of Hla Moleculesmentioning
confidence: 99%